Clarifying the absence of evidence regarding human health risks to microplastic particles in drinking-water: High quality robust data wanted - Gouin, Todd; Cunliffe, David; De France, Jennifer; Fawell, John; Jarvis, Peter; Koelmans, A. A. (Bart); Marsden, Peter; Testai, Emanuela E.; Asami, Mari; Bevan, Ruth; Carrier, R.; Cotruvo, Joseph; et al. (Elsevier, 2020)
In a recently published article, Leslie and Depledge (2020) raise concerns regarding statements on the risk that microplastic particles represent to human health and which have been attributed to reports published by both the Science Academies’ Group, Science Advice for Policy (SAPEA) (part of the European Commission’s Science Advice Mechanism) and the World Health Organization (WHO) (SAPEA. Science Advice for Policy by European Academies, 2019, WHO, 2019). Leslie and Depledge (2020), for instance, suggest that WHO (2019) conclude that there is ‘no evidence to indicate a human health concern.’ This statement, taken out of context from the WHO report (WHO, 2019), is then used to imply that the WHO conclude there is ‘no risk’ related to the exposure of microplastic particles (Leslie and Depledge, 2020). While, Leslie and Depledge (2020) highlight the importance of debate and systematic assessment of claims related to the assessment of risk, observations that we agree are important to highlight, there are a number of points raised in the article that require clarification.